Effect of yttrium iron garnet thick film in fabrication of flexible microstrip patch antenna - Hasan, Intan Helina; Hamidon, Mohd Nizar; Ismail, Alyani; Ismail, Ismayadi; Mohd Azhari, Nur Alin; Azhari, Saman; Mohd Kusaimi, Muhammad Asnawi; Osman, Rosiah (IEEE, 2019)
In this work, yttrium iron garnet (YIG) thick film paste was printed onto Kapton polyimide film to form a substrate overlay, which then a silver patch was printed onto it to form a flexible microstrip patch antenna (MPA). Measurement results showed that the flexible MPA with YIG thick film inclusion showed improved return loss, as well as having good stability when the MPA is being bent.